Business Training for Female Microenterprise Owners in Kenya Grew Their Firms without Harming Their Competitors - McKenzie, David; Puerto, Susana (World Bank, Washington, DC, 2017)
Business training is one of the most common support services offered by governments to small firms around the world. However, a number of evaluations of such training programs have struggled to identify impacts, and an additional concern has been that any growth of trained firms might at the expense of their competitors. In contrast, supporters of training programs argue that there might be positive benefits to other firms in the economy, if better business practices are like a technology that others can observe and copy, or if training encourages collective action. The authors designed an experiment to measure both the direct and spillover impacts of training.